The microtubule affinity regulating kinase MARK4 promotes axoneme extension during early ciliogenesis - Kuhns, Stefanie; Reymann, Jürgen; Neuner, Annett; Erfle, Holger; Boutros, Michael (The journal of cell biology, 2013)
Despite the critical contributions of cilia to embryonic development and human health, key regulators of cilia formation await identification. In this paper, a functional RNA interference-based screen linked 30 novel protein kinases with ciliogenesis. Of them, we have studied the role of the microtubule (MT)-associated protein/MT affinity regulating kinase 4 (MARK4) in depth. MARK4 associated with the basal body and ciliary axoneme in human and murine cell lines. Ultrastructural and functional analyses established that MARK4 kinase activity was required for initiation of axoneme extension. We identified the mother centriolar protein ODF2 as an interaction partner of MARK4 and showed that ODF2 localization to the centriole partially depended on MARK4. Our data indicated that, upon MARK4 or ODF2 knockdown, the ciliary program arrested before the complete removal of the CP110-Cep97 inhibitory complex from the mother centriole, suggesting that these proteins act at this level of axonemal extension. We propose that MARK4 is a critical positive regulator of early steps in ciliogenesis.